Transcriptome Profiles Reveal the Growth-Promoting Mechanisms of Paenibacillus polymyxa YC0136 on Tobacco (Nicotiana tabacum L.) - Liu, Hu; Wang, Jun; Sun, Huimin; Han, Xiaobin; Peng, Yulong; Liu, Jing; Liu, Kai; Ding, Yanqin; Wang, Chengqiang; Du, Binghai (Frontiers in Microbiology, 2020)
Paenibacillus polymyxa is an important member of the plant growth-promoting rhizobacteria. P. polymyxa YC0136 inoculation had beneficial effect on growth promotion and biological control of tobacco (Nicotiana tabacum L.) under field conditions. This study aimed to reveal the growth-promoting mechanisms of strain YC0136. In growth-promotion assays, tobacco plant height was increased by 8.42% and 8.25% at 60 and 90 days, respectively, after inoculation with strain YC0136. Strain YC0136 also promoted the accumulation of tobacco biomass in varying degrees. Following inoculation with strain YC0136, 3,525 and 4,368 tobacco genes were up-regulated and down-regulated, respectively. Strain YC0136 induced the expression of plant hormone-related genes in tobacco, including auxin, cytokinin, and gibberellin, as well as transcription factors related to stress resistance such as WRKY and MYB. In addition, strain YC0136 induced the up-regulation of genes in the phenylpropanoid biosynthesis pathway by 1.51-4.59 times. Interaction with tobacco also induced gene expression changes in strain YC0136, with 286 and 223 genes up-regulated and down-regulated, respectively. Tobacco interaction induced up-regulation of the ilvB gene related to auxin biosynthesis in strain YC0136 by 1.72 times and induced expression of some nutrient transport genes. This study contributes to our understanding of the growth-promoting mechanisms of strain YC0136 on tobacco and provides a theoretical basis for the application of P. polymyxa YC0136 as a biological fertilizer.